Book review: : Fukuyama F. Political Order and Political Decay: From the Industrial Revolution to the Globalization of Democracy. NY: Farrar, Straus and Giroux, 2014. 672 p. - Getahun Antigegn Kumie (RUDN Journal of Public Administration, 2020)
The review of Francis Fukuyama’s book “Political Order and Political Decay: From the Industrial Revolution to the Globalization of Democracy” examines the processes of political development and modernization. “Political Order and Political Decay” is the second volume of a large-scale study. Both books adhere to the paradigm that a successful liberal democracy combines three main elements: the state, the rule of law, and accountability - and the balance between them is crucial. Fukuyama recognizes that there is a link between economic prosperity and democracy but does not claim that one automatically leads to the other. Fukuyama believes that Chinese phenomenal economic growth combined with an authoritarian government will not be able to persist, but does not conclude that a democratic revolution in China is inevitable. Fukuyama also became disillusioned with the possibilities of exporting democracy. The author warns that political decline is more pronounced in the United States than in other democracies, because the latter have demonstrated a greater ability to adapt to changing circumstances.